2018
DOI: 10.3389/fnagi.2018.00098
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Hypofunction in Presbycusis-Related Tinnitus With Cognitive Function Impairment: Emerging Hypotheses

Abstract: Presbycusis (age-related hearing loss) is a potential risk factor for tinnitus and cognitive deterioration, which result in poor life quality. Presbycusis-related tinnitus with cognitive impairment is a common phenotype in the elderly population. In these individuals, the central auditory system shows similar pathophysiological alterations as those observed in Alzheimer’s disease (AD), including cholinergic hypofunction, epileptiform-like network synchronization, chronic inflammation, and reduced GABAergic inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 186 publications
1
12
0
Order By: Relevance
“…Although HL is associated with cognitive impairment, frailty, and motor dysfunction ( Chen et al, 2014 ; Panza et al, 2015 ; Kamil et al, 2016 ; Deal et al, 2017 ; Bang et al, 2020 ; Bonfiglio et al, 2020 ), identifying the causal relationship between HL and frailty phenotype and cognition decline is difficult because HL is similar to pre-MCI, with long subclinical period ( Golub et al, 2019 , 2020 ). Our results revealed that aging does not increase the severity of tinnitus and confirmed the reports of previous studies, which indicated that depression increases the risk for severe HL or tinnitus ( Shargorodsky et al, 2010 ; Langguth et al, 2013 ; House et al, 2018 ; Ruan et al, 2018 ; Jafari et al, 2019 ; Golub et al, 2020 ). Hypertension was a risk factor for tinnitus ( Shargorodsky et al, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although HL is associated with cognitive impairment, frailty, and motor dysfunction ( Chen et al, 2014 ; Panza et al, 2015 ; Kamil et al, 2016 ; Deal et al, 2017 ; Bang et al, 2020 ; Bonfiglio et al, 2020 ), identifying the causal relationship between HL and frailty phenotype and cognition decline is difficult because HL is similar to pre-MCI, with long subclinical period ( Golub et al, 2019 , 2020 ). Our results revealed that aging does not increase the severity of tinnitus and confirmed the reports of previous studies, which indicated that depression increases the risk for severe HL or tinnitus ( Shargorodsky et al, 2010 ; Langguth et al, 2013 ; House et al, 2018 ; Ruan et al, 2018 ; Jafari et al, 2019 ; Golub et al, 2020 ). Hypertension was a risk factor for tinnitus ( Shargorodsky et al, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…Apart from frailty phenotypes, age was the most significant independent risk factor for HL severity and HL with tinnitus. Previous epidemiological studies revealed that the prevalence of sensory and motor dysfunction and cognition deficit, frailty, and tinnitus increases with age ( Shargorodsky et al, 2010 ; Panza et al, 2015 ; Ruan et al, 2018 ; Jafari et al, 2019 ). Although HL is associated with cognitive impairment, frailty, and motor dysfunction ( Chen et al, 2014 ; Panza et al, 2015 ; Kamil et al, 2016 ; Deal et al, 2017 ; Bang et al, 2020 ; Bonfiglio et al, 2020 ), identifying the causal relationship between HL and frailty phenotype and cognition decline is difficult because HL is similar to pre-MCI, with long subclinical period ( Golub et al, 2019 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Presbycusis and dementia may share some common pathophysiological mechanisms [50,51] once degradation on one pathway may accelerate the degradation on each other disease. The hypothetical mechanistic pathways are still uncertain.…”
Section: The Association Between Presbycusis and Cognitive Declinementioning
confidence: 99%